1995
DOI: 10.1017/s0022377800018407
|View full text |Cite
|
Sign up to set email alerts
|

Non-stationary resonant Alfvén surface waves in one-dimensional magnetic plasmas

Abstract: This paper uses incompressible visco-resistive MHD to study the propagation of linear resonant waves in an inhomogeneous plasma. The background density and magnetic field are assumed to depend only on one spartial Cartesian coordinate, and the magnetic field is taken to be unidirectional and perpendicular to the direction of inhomogeneity. The equation that governs the component of the velocity normal to the plane formed by the direction of the inhomogeneity and the magnetic field is derived under the assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 26 publications
5
48
0
Order By: Relevance
“…We find the remarkable result that these jumps are the same as obtained for ideal and dissipative MHD (e.g., Sakurai et al 1991;Goossens et al 1995;Ruderman et al 1995). This means that ion-neutral collisions do not modify the jumps of the plasma perturbations across the resonant layer.…”
Section: Jump Conditionssupporting
confidence: 67%
See 1 more Smart Citation
“…We find the remarkable result that these jumps are the same as obtained for ideal and dissipative MHD (e.g., Sakurai et al 1991;Goossens et al 1995;Ruderman et al 1995). This means that ion-neutral collisions do not modify the jumps of the plasma perturbations across the resonant layer.…”
Section: Jump Conditionssupporting
confidence: 67%
“…Functions F (τ) and G(τ) play here the role of the universal functions found in a number of previous investigations of resonant waves in both stationary and non-stationary states and for different dissipative processes (see, e.g., Mok & Einaudi 1985;Goossens et al 1995;Ruderman et al 1995;Tirry & Goossens 1996;Erdélyi et al 1995;Wright & Allan 1996;Ruderman & Wright 1999;Vanlommel et al 2002). A comprehensive review on the importance and properties of the universal F (τ) and G(τ) functions can be found in Goossens et al (2011).…”
Section: Behavior Of Perturbations Around the Resonance Positionmentioning
confidence: 94%
“…This is clearly illustrated in a recent analytical seismological study by Goossens et al (2008) which complemented a fully numerical seismology investigation by Arregui et al (2007). The eigenfunctions in the thin dissipative layer can be described by the functions F(τ) and G(τ) defined by for the driven problem and the functionsF(τ) and G(τ) defined by Ruderman et al (1995) for the incompressible eigenvalue problem and by Tirry & Goossens (1996) for the compressible eigenvalue problem. In the dissipative layer the MHD kink waves are highly Alfvénic.…”
Section: Pressureless Flux Tubes With Non-uniform Densitymentioning
confidence: 87%
“…In view of that conclusion it is difficult to understand why a kink mode can be called fast as fast waves are absent from incompressible plasmas. The eigenfunctions in the thin dissipative layer can be described by the functionsF(τ) andG(τ) which were first introduced by Ruderman et al (1995) for non-stationary incompressible resonant Alfvén waves in planar plasmas. The conclusion is the same as in the previous section.…”
Section: Incompressible Mhd Waves On Non-uniform Flux Tubesmentioning
confidence: 99%
“…Ruderman et al 1995) Ruderman et al (1995) reconsidered the problem studied by Mok & Einaudi (1985) when this condition is not satisfied. They showed that, while the solution describing the plasma motion in the dissipative layer is very much different from that obtained for the driven problem, the damping rate of the surface mode remains the same.…”
Section: Introductionmentioning
confidence: 99%